Improving Energy Efficiency by Using Liquid Benzene in Production of Ethylbenzene from Ethylene and Benzene - Claudya Purnama Azrie; Dea Carmelita; Faiz Abhinaya Kusuma; Nabila Putri Azzahra (Journal of Chemical Engineering Research Progress, 2025)
The production process of ethyl benzene through the alkylation reaction between ethylene and benzene is a crucial stage in the petrochemical industry, especially as the main raw material in the synthesis of styrene. The development and optimization of this process are important to increase reaction efficiency, reduce production costs, and minimize environmental impacts. This study aims to optimize the operating parameters of the alkylation reactor in order to obtain high ethylene conversion and maximum selectivity to ethyl benzene. The methods used include kinetic reaction modeling, process simulation, and sensitivity analysis to variables such as temperature, pressure, and mole ratio of ethylene to benzene. The simulation results show that the optimum conditions are achieved at a temperature of 650°F, a pressure of 300 psig, and a mole ratio of 10:1, with ethylene conversion reaching 97,3% and ethyl benzene selectivity of 99,6%. In conclusion, this optimization approach has succeeded in increasing the efficiency of the ethyl benzene production process and can be applied on an industrial scale to improve profitability and operational sustainability.